Association of methylenetetrahydrofolate reductase (MTHFR) rs1801133 (677C>T) gene polymorphism with ischemic stroke risk in different populations: An updated meta-analysis - Zhao, Lili; Li, Tao; Dang, Meijuan; Li, Ye; Fan, Hong; Hao, Qian; Song, Dingli; Lu, Jialiang; Lu, Ziwei; Jian, Yating; Wang, Heying; Wang, Xiaoya; et al. (Frontiers in Genetics, 2023)
Background Recently, increasing evidence has implicated methylenetetrahydrofolate reductase (MTHFR) gene mutation as a risk factor for ischemic stroke (IS) in the general population. However, studies have been inconclusive and lack evidence on specific populations. We aim to determine whether the rs1801133 (NC_000001.11(MTHFR):g. 677C>T (p.Ala222Val) variant, we termed as MTHFR rs1801133 (677 C>T), is linked to an increased risk of IS in different age groups and ancestry groups. Methods Literature relevant to our study was found by searching the PubMed, Cochrane Library, Web of Science, EMBASE, and CNKI databases. A random effect model analysis was used to calculate the pooled odds ratio (OR) and 95% confidence interval (CI) to evaluate any possible association. We conducted a subgroup analysis based on the age and ancestry groups of the included populations. Results As of March 2022, 1925 citations had been identified in electronic databases; 96 studies involving 34,814 subjects met our eligibility criteria. A strong link was found between IS and the MTHFR gene rs1801133 (677C>T) polymorphism in all genetic models [dominant genetic model (OR = 1.47, 95%CI = 1.33–1.61, p < 0.001), recessive genetic model (OR = 1.52 95%CI = 1.36–1.71, p < 0.001), heterozygous model (OR = 1.36, 95%CI = 1.24–1.48, p < 0.001), homozygous model (OR = 1.82, 95%CI = 1.58–2.11, p < 0.001), and T allelic genetic model (OR = 1.37, 95%CI = 1.27–1.48, p < 0.001)]. Further subgroup analyses indicated that the MTHFR rs1801133 (677C>T) variant may increase the risk of IS in Asian, Hispanic or Latin population, middle-aged, and elderly populations (p＜0.001). Conclusion Our results implied that mutation of the T allele of MTHFR rs1801133 (677C>T) could be a risk factor for IS. A significant association was found among Asian, Hispanic or Latin population, middle-aged, and elderly people.